2013
DOI: 10.1111/obr.12067
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity are associated with musculoskeletal complaints as early as childhood: a systematic review

Abstract: In order to examine (i) the association between weight status and musculoskeletal complaints (MSC) in children, and (ii) whether overweight and obese children have a higher risk of developing MSC than normal-weight children Medline, Embase, Web of Science and Cochrane were searched (all years up to 2 January 2013) for observational studies studying direct associations between body mass index (or weight status) and MSC in children. Forty studies, together studying over one million children, were included. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
4
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 58 publications
3
144
4
6
Order By: Relevance
“…In contrast to our findings, previous literature reports that excess weight at a young age is already associated with specific health problems like musculoskeletal complaints22 and asthma 23. However, Wake et al 24 also found that overweight and obese adolescents do not report specific health complaints that might prompt them to see their doctor.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, previous literature reports that excess weight at a young age is already associated with specific health problems like musculoskeletal complaints22 and asthma 23. However, Wake et al 24 also found that overweight and obese adolescents do not report specific health complaints that might prompt them to see their doctor.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies, mostly carried out on population basis and in secondary healthcare settings, have shown that childhood overweight and obesity are associated with (in questionnaires reported) musculoskeletal complaints, injuries and fractures as early as childhood 2 3. The prevalence of musculoskeletal pain is 26% higher in overweight children compared with normal weight children, and the prevalence of injuries and fractures is 8% higher 2. In contrast with these findings, it has also been found that overweight children do not have an increased injury risk compared with normal weight sports participants 4.…”
Section: Introductionmentioning
confidence: 96%
“…[45][46][47] Current evidence points to a negative effect of obesity on the musculoskeletal health of children. [48][49][50][51] An increased body mass index in children has been identified as a predictor for musculoskeletal problems, with knee and foot pain the most commonly reported symptoms. [50][51][52][53] Children who are overweight or obese show alterations in standing balance, postural adjustment, and movement efficiency, which has been proposed to contribute to the development of lower limb angular deformities and premature osteoarthritis.…”
Section: Obesitymentioning
confidence: 99%